Words Don't Come Easy: How Male Prisoners' Difficulties Identifying and Discussing Feelings Relate to Suicide and Violence - Hemming, Laura; Bhatti, Peer; Shaw, Jennifer; Haddock, Gillian; Pratt, Daniel (Frontiers in Psychiatry, 2020)
Suicide and violence are prevalent within male prisons in the UK. It has been suggested that alexithymia may be associated with both suicide and violence. Alexithymia can be defined as an inability to identify or discuss emotions. The present study aimed to qualitatively explore male prisoners’ experiences of alexithymia and how these experiences may relate to suicide and violence. Fifteen male prisoners were recruited from two prisons in the North West of England. All participants had experienced suicidal and / or violent thoughts and / or behaviours in the past three months, and all screened positive on an established measure of alexithymia. Participants took part in a qualitative interview during which they were also given the opportunity to provide drawings of their emotions. Data were transcribed and analysed using thematic analysis, with a collaborative approach taken between researchers and an individual with lived experience of residing in prison. The results indicated that male prisoners tended not to talk about their emotions with others, due to external pressures of residing in prison in addition to internal difficulties with recognizing and articulating emotions. Not discussing emotions with others was associated with a build-up of emotions which could result in either an emotional overload or an absence of emotions. Both experiences were perceived to be associated with hurting self or others, however, participants also identified a ‘safety valve’ where it was acknowledged that using more adaptive approaches to releasing emotions could prevent harm to self and others. These findings suggest three main clinical implications; 1) a cultural shift in male prisons is needed which encourages open communication of emotions 2) individualized support is needed for those identified as experiencing a difficulty in recognizing and articulating emotions and 3) prison staff should encourage alternative ways of releasing emotions such as by using harm minimization or distraction techniques.